2019
DOI: 10.1021/acscatal.9b04768
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of β-Lactam via Palladium-Catalyzed Enantioselective Intramolecular C(sp3)–H Amidation

Abstract: β-Lactams are important scaffolds in drug design and frequently used as reactive intermediates in organic synthesis. Catalytic reactions featuring intramolecular C–H amidation of alkyl carboxamide substrates could provide a straightforward disconnection strategy for β-lactam synthesis. Herein, we report a streamlined method for asymmetric synthesis of β-aryl β-lactams from propanoic acid and aryl iodides via Pd-catalyzed sequential C­(sp3)–H functionalization. The lactam-forming reaction provides an example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 70 publications
1
56
0
2
Order By: Relevance
“…The successful enantioselective amidation of benzylic C(sp 3 )–H bonds led us to test the compatibility with unbiased aliphatic secondary C(sp 3 )–H bonds, a kind of more challenging substrates [3c,15] . Gratifyingly, we found that a variety of unbiased aliphatic carboxamides reacted efficiently when using ( S )‐3,3’‐fluorinated‐H8‐BINOL ( L9 ) as chiral ligand (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The successful enantioselective amidation of benzylic C(sp 3 )–H bonds led us to test the compatibility with unbiased aliphatic secondary C(sp 3 )–H bonds, a kind of more challenging substrates [3c,15] . Gratifyingly, we found that a variety of unbiased aliphatic carboxamides reacted efficiently when using ( S )‐3,3’‐fluorinated‐H8‐BINOL ( L9 ) as chiral ligand (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of 8‐aminoquinoline DG was also evaluated. Unfortunately, no amidation product was obtained under identical reaction conditions ( 2aa ), indicating the superior effect of PIP auxiliary in asymmetric functionalization of unbiased methylene C(sp 3 )−H bonds …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy has also been successfully employed for the direct esterification and amination of C-H bonds including benzylic C-H bonds under oxidative reaction conditions. Various transition-metals efficiently catalyzed the direct esterification [7,8] and amination [9][10][11] of C-H bonds. Due to the toxicity and cost of transition-metal catalysts, increasing interest has been paid on metal-free esterifications of benzylic C-H bonds.…”
Section: Introductionmentioning
confidence: 99%